2013
DOI: 10.1002/alr.21219
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional volumetric computed tomographic scoring as an objective outcome measure for chronic rhinosinusitis: clinical correlations and comparison to Lund‐Mackay scoring

Abstract: Background We aimed to test the hypothesis that 3-D volume-based scoring of computed tomographic (CT) images of the paranasal sinuses was superior to Lund-Mackay CT scoring of disease severity in chronic rhinosinusitis (CRS). We determined correlation between changes in CT scores (using each scoring system) with changes in other measures of disease severity (symptoms, endoscopic scoring, and quality of life) in patients with CRS treated with triamcinolone. Methods The study group comprised 48 adult subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 35 publications
6
60
0
Order By: Relevance
“…The results of this study are consistent with a growing trend in the literature that demonstrates the potential utility of volumetric assessment for staging sinus disease [13, 14, 16]. The goal of the present study was to develop a computerized approach to the CT-based volumetric quantification of sinonasal mucosal inflammation in order to enhance the utility of imaging for staging CRS.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The results of this study are consistent with a growing trend in the literature that demonstrates the potential utility of volumetric assessment for staging sinus disease [13, 14, 16]. The goal of the present study was to develop a computerized approach to the CT-based volumetric quantification of sinonasal mucosal inflammation in order to enhance the utility of imaging for staging CRS.…”
Section: Discussionsupporting
confidence: 84%
“…The significant correlation between patient symptoms and the MLM score makes MLM one of only a few scoring systems that has demonstrated such a relationship [15, 16, 27]. The MLM system benefits from its objective nature and continuous scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pallanch et al correlated changes in the percent of sinus opacification before and after triamcinolone treatment with changes in symptoms and endoscopic findings. 7 Sedaghat and Bhattacharyya incorporated Hounsfield units into LM scores in an attempt to better utilize density information from the CT images. 8 Both studies found that image scores better correlated with some (but not all) of the symptoms, suggesting the superiority of the objective software-based systems to subjective, visual scoring systems.…”
Section: Introductionmentioning
confidence: 99%